Levels of Urbanization in Bangalore Urban District of Karnataka, India - Puttalingaiah, Surendra; Irfan, Shahnin; Hanjagi, Ashok Devendrappa (European Publisher, 2019)
Urbanization is a process and good indicator of development of a region. Bangalore Urban district has been experiencing an abnormal rate of urban growth in terms of population explosion increase in urban centres. This paper studies about the shuffling trends and levels of urbanization in Bangalore Urban Districts of Karnataka. The study is based upon analysis of census data from 1901 to 2011. The entire study is based on Secondary data. Taluk is selected as basic unit of study investigation. As stated by 1901 Census data, the entire population of Bangalore Urban District was 3,84,601 which increased to 96,21,551 in 2011. The highest level of urbanization was seen in the year 1961 which was 17.7 %. While negative rate of urbanization was seen in the year 1971 i.e. -4.9%. The over most growth rate was seen in the year of 1951 that is 89.8% followed by 1981 i.e. 74.9 %. The rapid urbanization of Bangalore Urban District may raise many issues that might be positive and negative impact on the environment and even to human health and societal development. Thus, monitoring the trends and levels of urbanization will be a foremost task for the planners, administration, governmental and NGO’s for executing policies for the usage of resources and accommodate advancement simultaneously.